Influence of infused water cucumber to decrease blood pressure in elderly Hypertension: A Literature Review - Fauziah, Wardah; Kurniawan, Wawan; Wahyudin, Teguh (JURNAL NERS LENTERA, 2020)
The Elderly is a person over 60 years of age who is heavily at risk of Hypertesnia disease. Hypertension is an uncontagious disease, which has increased prevalence in Indonesia from 2013 to 2018. The purpose of this writing is to determine the influence of infused water cucumber on the decline in blood pressure in the elderly and to study the benefits of infused water cucumber. The search method of the library resource is done online using databases such as Google Scholar. The keywords used are "infused water", "hypertension", "elderly". The literature search is limited in the years 2010 to 2020. There are 4 research articles analyzed, Infused water is a combination of any fruit, vegetables, or herbal ingredients soaked in cold water. And has many advantages such as richer vitamins, more mineral-rich, more fresh and delicious water flavor, distinctive aroma, more attractive color. Cucumber (Cucumis sativus Linn) contains beneficial substances in health such as potassium, calcium, and magnesium. The results of this review literature are expected to be the basis for providing hypertensive drug escort intervention in the community as well as advanced research developers.